Isothiocyanate From Moringa oleifera Seeds Inhibits the Growth and Migration of Renal Cancer Cells by Regulating the PTP1B-dependent Src/Ras/Raf/ERK Signaling Pathway - Xie, Jing; Qian, Ying-Yan; Yang, Yang; Peng, Lin-Jie; Mao, Jia-Ying; Yang, Ming-Rong; Tian, Yang; Sheng, Jun (Frontiers in Cell and Developmental Biology, 2022)
Moringa oleifera Lam. is a tropical and subtropical plant that has been used for centuries as both food and traditional medicine. 4-[(α-L-Rhamnosyloxy) benzyl] isothiocyanate (MIC-1) is an active substance in M. oleifera, with anti-cancer activity. However, whether MIC-1 exerts anti-renal cancer effects is unknown. Consequently, the aim of the present study was to evaluate the effects of MIC-1 on the growth and migration of renal cell carcinoma (RCC) cells and to identify the putative underlying mechanism. We found that, among 30 types of cancer cells, MIC-1 exerted the strongest growth inhibitory effects against 786-O RCC cells. In addition, MIC-1 (10 μM) significantly inhibited the growth of five RCC cell lines, including 786-O, OSRC-2, 769-P, SK-NEP-1, and ACHN cells, but was not toxic to normal renal (HK2) cells. At the same time, MIC-1 suppressed 786-O cell and 769-P cell migration and invasion abilities, and reduced the expression of matrix metalloproteinase (MMP)-2 and MMP-9. Furthermore, MIC-1 induced apoptosis and cell cycle arrest in 786-O cells and 769-P cells, increased the Bax/Bcl-2 ratio, and decreased protein expression of CDK2 in 786-O cells. Molecular docking and small-molecule interaction analyses with PTP1B both showed that MIC-1 inhibited PTP1B activity by binding to its active site through hydrogen bonding and hydrophobic interactions. Additionally, MIC-1 could suppress the growth and migration of 786-O cells by inhibiting the PTP1B-mediated activation of the Src/Ras/Raf/ERK signaling pathway. In vivo experiments further showed that MIC-1 markedly inhibited the growth of xenograft tumors in mice, and greatly increased the Bax/Bcl-2 ratio in tumor tissues. In addition, MIC-1 had no effect on the PTP1B-dependent Src/Ras/Raf/ERK signaling pathway in HCT-116 cells, Hep-G2 cells, and A431 cells. Overall, our data show that MIC-1 could be promising non-toxic natural dietary supplement for the prevention and treatment of renal cancer.